Provenance, viability and physical quality in seeds of Panicum maximum ‘Mombasa’ - de Oliveira Cruz, José (Revista Ciência Agronômica, 2021)
Identifying areas that would enable the production of highly pure and viable seeds is important for the logistics of companies that act in the seed sector. The aim of the present study was to evaluate the effect of provenance on the viability and physical quality of seeds of Panicum maximum ‘Mombasa’. Nineteen seed batches from the states of São Paulo (six from Auriflama and three from Guzolândia) and Goiás (eight from Quirinópolis and two from Serranópolis) were evaluated using the following parameters: water content, viability by tetrazolium test, physical purity, PLS, 1000-seed weight and number of other seeds. Physical quality and viability in seeds of P. maximum ‘Mombasa’ are affected by their provenance. All the seed batches showed a sufficient level of viability to meet marketing standards. Based on physical purity, seed samples from Quirinópolis, Goiás should not be marketed. Based on an examination of noxious seeds, 85% of the seed samples are suitable for marketing.